Come ordinare il caos. Piccola introduzione alla filosofia morale - Ricci Sindoni, Paola (Filosofia Morale/Moral Philosophy, 2022)
Faced with the complexity of the present, both on the level of the multiplicity of philosophical orientations and on that of the crudeness of historical events, further work of thought is required, especially when dealing with the fatigue of practical orientation, typical of moral philosophy. For these reasons, ethics has above all the critical task of avoiding the total assimilation of the dynamics of human life to scientific procedures. Algorithms and big data, in fact, risk configuring a univocal world view, aimed at interpreting all the dimensions of reality as a whole. Reading the world with the only logical tool of mathematics can elude the many questions inherent in the irreducible singularity of the human living, in its complex social relationships. Recovering the space of philosophical reflection therefore means elaborating a different scenario, that is, a conceptual framework nourished by reasonableness and creative imagination: they seem to recall on the one hand the Aristotelian need for the enlightened exercise of practical wisdom and on the other the Kantian criterion of ‘ universality of the norm, as sources that purify the reasons for the action.